Grassland protection policy in China: Post-Wenchuan economic and environmental change in Aba prefecture, Sichuan Province. Issue 139 (January 2023) - Veeck, Gregory
Abstract: On May 12, 2008, southern Aba prefecture in north-central Sichuan was devastated by the M8.0 Wenchuan earthquake. A massive multi-year central government environmental mitigation effort resulted in economic revitalization based largely on the development of nature- and ethnic- tourism and the expansion of production from agriculture and husbandry. Concurrently, however, management of pasture areas was largely removed from local control and ceded to provincial and national environmental managers who instituted many draconian measures intended to protect pasture areas from further degradation while significantly restricting access by local pastoralists. Results of fieldwork, and subsequent analyses of archived data, indicate the strict enactment and enforcement of new environmental regulations with limited local input radically altered the local economy including the structure of husbandry activities, expanded tourism and crop production and shifted residence patterns. These policy interventions that excluded local stakeholders also increased income inequality and drastically reduced the practice of transhumant pastoralism which in turn created new ecological challenges. Highlights: Study of Aba Sichuan identifies expected and unexpected outcomes of environmental and economic policies post-2008 earthquake. Local control of environmental and economic policy in west China is lost if funding is from central government sources. Investment in tourism infrastructure in Tibetan areas of China aids local economy but speeds erosion of traditional culture.